SOVEREIGN SUBJECT AND PROTECTED LANGUAGE - Giraldo Giraldo, Ana María (Disertaciones, 2017)
The purpose of this text is to evidence that the critic to legal interpretation of offensive speech made by Judith Butler becomes stronger analyzing properly the illocutionary acts. First of all, the text presents the two notions in which Butler’s critic relies on. It is necessary to clarify in this part the difference between the illocutionary speech acts and performative utterances. This is because Butler uses both notions without different use. In second place, the paper shows a dialogue that the author maintains with Nietzsche, Robert Cover and Derrida. From these authors, Butler takes some ideas and rejects some others to form her definite conclusion. Finally, this paper defends that the Butler’s argument has two inaccuracies that have to be resolved in order to reinforce her position.
Keywords: illocitionary act; performative utterances; Judith Butler; protected language